Emotional Intelligence on Self-Efficacy among the Senior Secondary Students of Barak Valley, Assam - Monali Debnath; Dr. Naresh Kumar (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Abstract: In the present dynamic and constantly changing culture, emotional intelligence is crucial for adolescents to lead better lives in all areas of schooling. Consequently, the goal of this research is to comprehend how emotional intelligence influences self-efficacy among the senior secondary students of Barak Valley, Assam. The study is quantitative in nature, and it collects pertinent data from the students using a descriptive survey method. To collect appropriate data the sampling procedure used purposive sampling to select the school and random sampling to select the students. The total sample size of the study is calculated as 216 including students from both private and public schools. The findings of the study were calculated with the use of Excel and SPSS and found to have a significant difference and relationship among the learners based on the t-test and Pearson correlation acquired results